1995
DOI: 10.1007/bf00400731
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering therapy may retard the progression of diabetic nephropathy

Abstract: There is experimental evidence to suggest that hypercholesterolaemia may play a pathogenetic role in progressive glomerular injury. We investigated the effect of cholesterol-lowering therapy on the progression of diabetic nephropathy in 34 patients with non-insulin-dependent diabetes mellitus. Patients were randomly assigned in a single-blind fashion to treatment with either lovastatin, an HMG CoA reductase inhibitor (n = 16; mean dose 30.0 +/- 12.6 mg/day) or placebo (n = 18) for 2 years. Renal function was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
1
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(86 citation statements)
references
References 35 publications
2
81
1
2
Order By: Relevance
“…Recently, Lam et al [10] demonstrated that cholesterol-lowering therapy retarded the progression of nephropathy in NIDDM, reducing the rate of impairment of kidney function, without affecting the albumin excretion rate [10]. This finding can also be interpreted as evidence for a major role for macroangiopathy in the evolution towards ESRF in NIDDM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lam et al [10] demonstrated that cholesterol-lowering therapy retarded the progression of nephropathy in NIDDM, reducing the rate of impairment of kidney function, without affecting the albumin excretion rate [10]. This finding can also be interpreted as evidence for a major role for macroangiopathy in the evolution towards ESRF in NIDDM.…”
Section: Discussionmentioning
confidence: 99%
“…While abnormalities of serum lipids are common in patients with type 2 diabetes and persistent albuminuria, some recent prospective studies document an association of high baseline level of serum cholesterol with an increased risk of developing incipient or overt nephropathy in patients with type 2 DM. 20,23 Moreover, Lam et al 24 have reported that lovastatin, a cholesterol-lowering drug, slows the progression of nephropathy in type 2 DM. If larger studies confirm these results, hypercholesterolemia should also be treated aggressively in patients with type 2 DM and microalbuminuria.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There is little evidence that treatment of dyslipidaemia will offer any protection of renal function, and the few studies that do exist are somewhat conflicting. [43][44][45][46] Obviously, treatment of dyslipidaemia is more important for the prevention of cardiac and vascular disease. 22 Only a few studies have assessed the use of lowprotein diets in diabetic patients.…”
Section: Microalbuminuria In Type 2 Diabetesmentioning
confidence: 99%